Organoleptic and Physicochemical Profile Comparison of Cow Milk Yogurt and 'Eggurt' Made from Different Egg Whites - Ridawati, Ridawati; Alsuhendra, Alsuhendra (Poltanesa, 2024)
Yogurt is a widely consumed fermented dairy product known for its distinctive flavor, nutritional value, and health benefits. To expand its nutritional profile and enhance textural qualities, this study explores the use of egg whites as an alternative ingredient in yogurt production. The research compares the sensory and physicochemical properties of traditional milk yogurt with "eggurt" a yogurt variant made using different egg white sources: free-range chicken, caged chicken, and duck eggs. Four samples were prepared, including one control (milk yogurt) and three “eggurt” variants. Sensory quality was evaluated through organoleptic testing using a structured Likert scale to assess attributes such as color, surface gloss, aroma, mouthfeel, and flavor. Physicochemical analysis included moisture content, total dissolved solids, viscosity, ash content, and acidity measurements. Results showed that free-range “eggurt” was most like milk yogurt in terms of texture and flavor, displaying balanced viscosity and minimal surface liquid separation. In contrast, caged “eggurt” exhibited increased surface liquid, higher ash content, and stronger acidity, while duck eggurt was noted for its excessive thickness, very high viscosity, and pronounced acidity. These textural and compositional differences, despite the higher production costs, suggest that free-range “eggurt” is the most promising alternative, offering a comparable sensory experience to traditional yogurt while enhancing texture and overall quality.